2015
DOI: 10.1176/appi.ps.201400185
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Reduction of Seclusion and Restraint and Assaults by Patients in Pennsylvania’s State Hospitals

Abstract: Objective: This prospective study assessed the use of seclusion and restraint in the Pennsylvania state hospital system from 2001 through 2010. It also examined the correlation between declining use of containment procedures and assaults by patients on other patients and staff.Methods: The 12,900 anonymized records involving the 1,801 unique, civilly committed individuals who were physically or mechanically restrained and secluded in the nine civil hospitals during this study period were entered into a databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 8 publications
2
21
0
3
Order By: Relevance
“…), although other research indicates restraint reduction is not necessarily associated with an increase in aggression (Smith et al . ). Further, existing research draws attention to the incidence of posttraumatic stress in nurses working in acute psychiatric inpatient settings being about 10% (Jacobowitz ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), although other research indicates restraint reduction is not necessarily associated with an increase in aggression (Smith et al . ). Further, existing research draws attention to the incidence of posttraumatic stress in nurses working in acute psychiatric inpatient settings being about 10% (Jacobowitz ).…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, research has also reported that reduction in the use of restrictive practices does not lead to an increase in assaults (Smith et al . ). Building on these successes, the Restrictive Practice Working Group of the Australian Health Ministers’ Advisory Council developed the ‘National Principles to Support the Goal of Eliminating Mechanical and Physical Restraint in Mental Health Services’ () as the next logical step towards eliminating restrictive practices in Australia.…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, nurses have also reported to often feel relieved after the seclusion is over and concerned whether they did the right thing or failed to find alternative methods [33]. Researchers still disagree whether decreasing the use of seclusion results in increasing of violent incidents [39] or whether it has no effect [40] or a decreasing effect [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Notably, levels of PRN use vary in different organizations (Baker et al 2008a;Molloy et al 2012) and some hospitals have successfully discontinued the use of psychotropic PRN (Smith et al 2015). Evidence exists that reducing PRN does not increase aggressive incidents (Friedman et al 2012;Hayes & Russ 2015;Smith et al 2008).…”
Section: Discussionmentioning
confidence: 99%